Condutividade iônica e eletrônica em vidros 0,50[xAg2O(1-x)V2O5].0,50P2O5 - Diaz Marin, Juan Jairo (2016)
Mixed conductive glassy materials have in their composition, in addition to a glass former, a metallic element in two oxidation states and ions with high mobility, generally alkaline or Ag+ ions. These materials can be used in solid state batteries. However, from a scientific point of view, there are still some issues to be solved, such as the mechanism that best explains the behavior of electric conduction in these materials, and why there is a marked drop in conductivity as a function of composition, for equimolar compositions between the modifier that introduces the ionic conduction, and the transition metal oxide that introduces the electronic conduction. Therefore, to advance the frontier of knowledge about the conduction mechanisms present in mixed conductive glasses, the ternary system of the glass family 0.50[xAg2O(1-x)V2O5].0.50P2O5, (0 ≤ x ≤ 1) was chosen. Each vitreous composition was synthesized and characterized by X-ray diffraction, differential scanning calorimetry, Helium pycnometry, and impedance spectroscopy. The impedance spectroscopy measurements of the composition x=0.6 revealed a semicircle with a deformation at low frequency. This semicircle cannot be adjusted by a single RC circuit. The analysis of the pre-exponential factor and the activation energies of the glasses shows lower values for the glasses rich in vanadium, that is, in the "electronic" region, when compared to the pre-exponential factor of the glasses of the region richest in silver, or in the "ionic" region. This behavior is in accordance with the theoretical expressions for each of the conductivity mechanisms. In an attempt to quantify the ionic and electronic contributions, the electromotive force method (F.E.M) was applied. This method was selected because, theoretically, it allows a precise quantification of the electronic and ionic conductivities. However, the experimental results showed that the generated electrochemical cell did not correspond to the expected one, therefore it was not possible to quantify the ionic and electronic contributions to the total electrical conductivity.